2020
DOI: 10.2967/jnmt.120.250282
|View full text |Cite
|
Sign up to set email alerts
|

Dose Optimization in 18F-FDG PET Based on Noise-Equivalent Count Rate Measurement and Image Quality Assessment

Abstract: The present study aimed to optimize the injected dose of 18 F-FDG in whole-body PET/CT scans and assess its effect on noise-equivalent count rate (NECR) and visual image quality (IQ). Methods: Patients scheduled to undergo 18 F-FDG PET/ CT were prospectively recruited in the study from January to December 2019, regardless of the indication or underlying disease. Patients were divided into 4 groups and injected with different amounts of 18 F-FDG radioactivity per kilogram of body weight (1.85, 3.7, 5.5, and 7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Based on the excellent intra-and inter-agreement agreement (all kappa > 0.85), the mean threshold SNR L was 11.2 for acceptable image quality of 68 Ga-DOTA-TATE total-body PET/CT. Compared with 18 F-FDG images we previously analyzed, the threshold SNR of 14.0 was slightly higher. The difference was consistent with a previous study in which the acceptable SNR L was 6.2 for whole-body 68 Ga-DOTATATE PET/CT, but 18 F-FDG studies have revealed a higher SNR of 10 [19].…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Based on the excellent intra-and inter-agreement agreement (all kappa > 0.85), the mean threshold SNR L was 11.2 for acceptable image quality of 68 Ga-DOTA-TATE total-body PET/CT. Compared with 18 F-FDG images we previously analyzed, the threshold SNR of 14.0 was slightly higher. The difference was consistent with a previous study in which the acceptable SNR L was 6.2 for whole-body 68 Ga-DOTATATE PET/CT, but 18 F-FDG studies have revealed a higher SNR of 10 [19].…”
Section: Discussionmentioning
confidence: 70%
“…Image quality is commonly evaluated by the metric SNR or noise equivalent count rate (NECR). The SNR is calculated as the value of the square root of the product of system sensitivity, injected activity, and acquisition time [ 13 ], whereas the NECR is calculated as the ratio of the square of the true events to the total of true events, random events, and scatter coincidences [ 18 ]. A constant value of SNR and NECR can overcome the limitation of patient-specific attenuation to render uniform image quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations